Transformasi Kepemimpinan Gembala Sidang di Era 5.0: Antara Otoritas Spiritual dan Kecakapan Digital - Ibrahim, Ibrahim; Ronny, Oei (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2025)
The Industrial Revolution 5.0 has brought significant disruption in various aspects of life, including in the structure and leadership patterns of the church. Digital transformation requires congregational pastors to adopt new approaches, both in communication, church nurturing, and in reunderstanding spiritual authority in the midst of an ever-evolving virtual reality. This article aims to analyze relevant forms of congregational pastoral leadership in the digital age by emphasizing the importance of a balance between spiritual authority and digital competence. This study uses a qualitative-descriptive approach with theological analysis methods and contextual reflection to formulate theological implications and practical strategies for local churches. The results of the analysis show that congregational pastors need to develop contextual spirituality in the digital space, implement participatory leadership patterns in the online ecosystem, and lead the church collectively in innovation rooted in gospel values. This article recommends strategies in the form of sustainable digital coaching, hybrid ministry reorganization, and the formation of a theological and adaptive church culture in response to the dynamics of the digital age.